RELIABILITY AND RESPONSIVENESS OF MUSCULOSKELETAL ULTRASOUND IN SUBJECTS WITH AND WITHOUT SPINAL CORD INJURY - Dudley-Javoroski, Shauna (2010)
Rehabilitation after spinal cord injury (SCI) aims to preserve the integrity of the paralyzed musculoskeletal system. The suitability of ultrasound (US) for delineating training-related muscle/tendon adaptations after SCI is unknown. The purpose of this study was to quantify within- and between-operator reliability for US and to determine its responsiveness to post-training muscle/tendon adaptations in SCI subjects. Two novice operators and one experienced operator obtained sonographic images of the vastus lateralis, patellar tendon, soleus, and Achilles tendon from 7 SCI subjects and 16 controls. For control subjects, within-operator concordance (ICC(3,1)) ranged from 0.58 to 0.95 for novice operators and exceeded 0.86 for the experienced operator. Between-operator concordance (ICC (2,1)) ranged from 0.62 to 0.74. Ultrasound detected muscle hypertrophy (p < 0.05) following electrical stimulation training in subjects with SCI (responsiveness), but did not detect differences in tendon thickness. These error estimates support the utility of US in future post-SCI training studies.